AN INVESTIGATION INTO THE DISCIPLINARY PRACTICES THAT INFLUENCE THE STUDENT UNREST IN PUBLIC SECONDARY SCHOOLS IN MERU COUNTY, KENYA - Marete, Jacob Bundi; Mugwe, Dr. Mary; Reche, Prof. George N. (IJRDO- Journal of Educational Research, 2017)
Since Kenya attained independence in 1963, students’ unrest in public secondary schools has been on the rise, and thus students’ academic achievements and subsequently the economic progress of Kenya has suffered the negative consequences of strikes. The purpose of the study was to investigate the disciplinary factors that influence the student unrest in public secondary schools in Meru County, Kenya. The research found that most schools do not follow progressive discipline practices, and most schools did not have discipline committees where students who felt unfairly treated can appeal the decision. Most of the disciplinary was done by student leadership councils, and all public secondary school had rules and regulations that are known by staff members and students.